Introduzione - Tarantino, Daniela (Vergentis, 2024)
The analyses proposed in this volume are aimed at a wider understanding of the principles of law and at dialogue between the sciences in order to counteract the bad knowledge that allows individuals, societies and States to justify all forms of abuse and manipulation of the environment. In fact, it has value in that, emancipated from the myths of modernity, it favours the development and promotion of peoples, recovering that rational way of life which respects the dignity of the human person and the beauty of nature.